Supraventricular arrhythmias - Gwizdała, Adrian; Straburzyńska-Migaj, Ewa (Lekarz POZ, 2017)
Supraventricular arrhythmia, including paroxysmal supraventricular tachycardia, is a common arrhythmia observed in general population. The prevalence of specific arrhythmia types depends on patient age, sex and comorbidities. Implementation of effective therapy, including catheter ablation, requires prior ECG documentation of arrhythmia or its induction during clinical challenges. Effective management of patients with supraventricular tachycardia involves cooperation between primary care physicians and cardiologists.